"What we need is a better world to live in!". Interview with Professor Amit Bhaduri - Amit Bhaduri (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2005)
First paragraph: You are an economist who has done research at a lot of locations and universities all over the world. Is there a common culture of scientific research? What is common, what is different with regard to doing research in Delhi, Cambridge, or Berlin?
Keywords: 330